THE SHARIA COMPLIANCE OF SECURITIES CROWDFUNDING: A CASE STUDY ON SME - Wardah Yuspin; Iramadya Dyah Marjanah; Arief Budiono; Jompon Pitaksantayothin (Fakultas Hukum, Universitas Diponegoro, 2023)
The growth and development of Small Medium Enterprises (SME) have various challenges that must be overcome. Financing is one of the most challenging issues to be funded. Traditional finance is a funding instrument that is somewhat difficult to penetrate for SME as they are not yet bankable and are in the stage of business initiation. This is resolved by the stipulation of POJK regulation Number 37/POJK.04/2018 which was amended to POJK Number 16/POJK.04/2021 and becomes alternative funding for SME in Indonesia. This study uses emipirical research method with a qualitatif study approach. Primary data was obtained based on interviews and secondary data using desk research. There are two products issued by Securities Crowdfunding Sharia: Shares and Sukuk. These two products must fulfill the requirements of sharia principles, which should not incorporate with syariah compliance. The result of this research is that the products in SCF Syariah do not violate Sharia Compliance. Four categories have been analyzed, and the results show that they do not contain four categories that violate Sharia Compliance.